The Annexation of the Districts of Javorina and Lesnice by Poland in 1938–1939 (Theatrum historiae, 2015)
Poland made use of the situation of Czecho-Slovakia after the Munich Agreement and made a request for the territory of the Těšín Region. Initially, Poland made no request for the Slovak territory. Later, Warsaw changed its mind and called for the ceding of the part of Spiš, Orava and Kysuce. Poland held the opinion that the local Goral inhabitants were the Poles, despite the fact that the majority of them reported to the Slovak nationality. Thus Poland acquired the districts of Javorina and Lesnica (in the Spiš Region) in November 1938. The attitude of the local inhabitants to the seceding from Slovakia, and the subsequent Polish pressure, was negative. On 1st September1939, after the German attack on Poland, which the Slovak Army was involved in too, Javorina and Lesnica became a part of Slovakia again.
Keywords: Slovak-Polish relations; 1938–1939; Javorina; Lesnica; Spiš